Long-range sequencing revealed a new KIR3DL1*0150204 allele in 20 individuals of Asian descent - Yindom, L; Wang, L; Dong, T; Rowland-Jones, S (2014)
The novel KIR3DL1*0150204 has four point mutations: 3037G>A, 4115A>G, 6053G>C, and 8034A>G compared to KIR3DL1*0150201. © 2014 John Wiley and Sons A/S.